PERAN KEPUASAN PELANGGAN MEMEDIASI PENGARUH PROMOSI PENJUALAN TERHADAP LOYALITAS PELANGGAN (Studi Komparasi antara GoFood dan GrabFood) - Girsang, Neri Parasian; Raka Sukawati, Tjokorda Gde; Warmika, I Gde Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
This study compares GoFood and GrabFood services to determine the relationship between sales promotion and customer loyalty as mediated by customer satisfaction. This study was carried out in Denpasar City, using a purposive sampling strategy, with an overall sample size of 100 GoFood and GrabFood customers. The data was collected using a survey approach, with a questionnaire as the study instrument. The collected data were analyzed using path analysis, Sobel test and Wilcoxon signed rank test. According to the outcomes of the analysis, it was discovered that sales promotion positively and significantly influence customer satisfaction and customer loyalty. Customer satisfaction positively and significantly influence customer loyalty. Customer satisfaction is a partially mediating variable for the influence of sales promotion on customer loyalty.There is a significant difference between the attractiveness of sales promotions, the level of satisfaction and the level of customer loyalty between GoFood and GrabFood.